The New Educational Frontier: Agentic AI's Evolutionary Journey Through The Lens of SPAR-4-SLR - Sugeng Rifqi Mubaroq; Mokhamad Arfan Wicaksono; Sherly Rahmawati; Iyan Gustiana; Meiry Akmara Dhina (VOCATECH: Vocational Education and Technology Journal, 2025)
AbstractThe emergence of Agentic Artificial Intelligence (AI) represents a fundamental transformation in educational technology, characterized by systems capable of autonomous, adaptive, and proactive operation. This systematic literature review employs the SPAR-4-SLR methodology to analyze 281 publications from Scopus, with 251 articles retained after temporal filtering (2010-2024), revealing the evolutionary trajectory of Agentic AI in education. The analysis identifies three distinct evolutionary eras: the Early Era (2010-2015) characterized by rule-based intelligent tutoring systems exhibiting proto-agentic behaviors, the Transitional Era (2016-2019) marked by enhanced adaptive systems leveraging learning analytics and machine learning, and the Agentic Era (2020-2024) distinguished by sophisticated autonomous systems powered by Large Language Models. Through integrated bibliometric, co-occurrence network, and thematic analyses, the study establishes a conceptual framework encompassing five defining characteristics of Agentic AI: learning initiative, dynamic adaptability, multi-modal interaction, persistence and memory, and collaboration with human actors. Co-citation network analysis reveals the intellectual structure connecting foundational intelligent tutoring research to contemporary generative AI applications. Despite exponential growth in publications, significant gaps persist in theoretical conceptualization of agency, longitudinal impact evidence, and implementation across diverse educational contexts, particularly at primary education levels. This study provides a comprehensive research agenda addressing theoretical, methodological, and implementation gaps to advance the effective and equitable development of Agentic AI in education. AbstrakKemunculan Agen Artificial Intelligence (AI) merepresentasikan transformasi fundamental dalam teknologi pendidikan, yang dicirikan oleh sistem yang mampu beroperasi secara otonom, adaptif, dan proaktif. Tinjauan literatur sistematis ini menggunakan metodologi SPAR-4-SLR untuk menganalisis 281 publikasi dari Scopus, dengan 251 artikel dipertahankan setelah penyaringan temporal (2010-2024), mengungkap trajektori evolusi Agen AI dalam pendidikan. Analisis mengidentifikasi tiga era evolusi yang berbeda: Era Awal (2010-2015) yang dicirikan oleh sistem tutoring cerdas berbasis aturan yang menunjukkan perilaku proto-agentik, Era Transisional (2016-2019) yang ditandai oleh sistem adaptif yang memanfaatkan analitik pembelajaran dan pembelajaran mesin, dan Era Agentik (2020-2024) yang dibedakan oleh sistem otonom yang canggih dan didukung oleh Model Bahasa Besar. Melalui analisis bibliometrik, jaringan ko-okurensi, dan tematik yang terintegrasi, studi ini menetapkan kerangka konseptual yang mencakup lima karakteristik pendefinisi Agen AI: inisiatif pembelajaran, adaptabilitas dinamis, interaksi multi-modal, persistensi dan memori, serta kolaborasi dengan aktor manusia. Analisis jaringan ko-sitasi mengungkap struktur intelektual yang menghubungkan penelitian tutoring cerdas fundamental dengan aplikasi AI generatif kontemporer. Meskipun terjadi pertumbuhan eksponensial dalam publikasi, kesenjangan signifikan masih tetap ada dalam konseptualisasi teoretis mengenai agensi, bukti dampak longitudinal, dan implementasi di berbagai konteks pendidikan, khususnya pada tingkat pendidikan dasar. Studi ini menyediakan agenda penelitian komprehensif yang mengatasi kesenjangan teoretis, metodologis, dan implementasi untuk memajukan pengembangan Agen AI yang efektif dan berkeadilan dalam pendidikan.